Cinnarizine versus Topiramate in Prophylaxis of Migraines among Children and Adolescents: A Randomized, Double-Blind Clinical Trial - ASHRAFI, Mahmoud Reza; NAJAFI, Zeinab; SHAFIEI, Masih; HEIDARI, Kazem; TOGHA*, Mansoureh (Iranian Journal of Child Neurology, 2014)
How to Cite This Article: Ashrafi MR, Najafi Z, Shafiei M, Heidari K, Togha M. Cinnarizinev ersus Topiramate in Prophylaxis of Migraines among Children and Adolescents: A Randomized, Double-Blind Clinical Trial. Iran J Child Neurol. 2014 Autumn;8(4): 18-27. Abstract Objective Migraines, a common health problem in children and adolescents, still do not have an FDA approved preventive treatment for patients under the age of 18 years. This study compares and contrasts the efficacy and safety of cinnarizine and topiramate in preventing pediatric migraines. Materials & Methods In this randomized, double-blind clinical trial 44 migrainous (from 4–15 years of age) were equally allocated to receive cinnarizine or topiramate. The primary efficacy measure was monthly migraine frequency. Secondary efficacy measures were monthly migraine intensity and ≥ 50% responder rate. Efficacy measures were recorded at the baseline and at 4, 8, and 12 weeks of treatment. Results During the double-blind phase of the study, monthly migraine frequency and intensity were significantly decreased in both the cinnarizine and topiramate groups when compared to the baseline. However, at the end of the study, the cinnarizine group exhibits a significant decrease from the baseline in the mean monthly migraine intensity when compared to the topiramate group (4.7 vs. 3, respectively; 95% CI = -0.8 to -3.2). Conclusion No significant difference between cinnarizine and topiramate was found for the prevention of pediatric migraines. Both treatments were well tolerated. References Hershey AD, Winner PK. Pediatric Migraine: Recognition and Treatment. J Am Osteopath Assoc. 2005;105:2S-8. Lewis DW, Yonker M, Winner P, Sowell M. The treatment of pediatric migraine. Pediatric Annals. 2005;34:448-460. Abu-Arefeh I, Russell G. Prevalence of headache and migraine in schoolchildren. BMJ. 1994;309:765-769. Linet MS, Stewart WF, Celentano DD, Ziegler D, Sprecher M. An Epidemiologic Study of Headache among Adolescents and Young Adults. JAMA: The Journal of the American Medical Association. 1989;261:2211-2216. Stewart WF, Linet MS, Celentano DD, Van Natta M, Ziegler D. Age- and sex-specific incidence rates of migraine with and without visual aura. Am J Epidemiol. 1991;134:1111-1120. Stewart WF, Lipton RB, Celentano DD, Reed ML. Prevalence of Migraine Headache in the United States. JAMA: The Journal of the American Medical Association. 1992;267:64-69. Split W, Neuman W. Epidemiology of Migraine among Students from Randomly Selected Secondary Schools in Lodz. Headache: The Journal of Head and Face Pain. 1999;39:494-501. Hershey AD, Kabbouche MA, Powers SW. Treatment of pediatric and adolescent migraine. Pediatr Ann. 2010;39:416-423. Hershey AD, Powers SW, Vockell AL, LeCates S, Kabbouche MA, Maynard MK. PedMIDAS: development of a questionnaire to assess disability of migraines in children. Neurology. 2001;57:2034-2039. Lewis D, Ashwal S, Hershey A, Hirtz D, Yonker M, Silberstein S. Practice Parameter: Pharmacological treatment of migraine headache in children and adolescents. Neurology. 2004;63:2215-2224. Brandes JL, Saper JR, Diamond M, et al. Topiramate for Migraine Prevention. JAMA: The Journal of the American Medical Association. 2004;291:965-973. Lakshmi CVS, Singhi P, Malhi P, Ray M. Topiramate in the Prophylaxis of Pediatric Migraine: A Double-Blind Placebo-Controlled Trial. Journal of Child Neurology. 2007;22:829-835. Lewis D, Winner P, Saper J, et al. Randomized, Double- Blind, Placebo-Controlled Study to Evaluate the Efficacy and Safety of Topiramate for Migraine Prevention in Pediatric Subjects 12 to 17 Years of Age. Pediatrics. 2009;123:924-934. Winner P, Pearlman EM, Linder SL, et al. Topiramate for Migraine Prevention in Children: A Randomized, Double-Blind, Placebo-Controlled Trial. Headache: The Journal of Head and Face Pain. 2005;45:1304-1312. Winner P, Gendolla A, Stayer C, et al. Topiramate for Migraine Prevention in Adolescents: A Pooled Analysis of Efficacy and Safety. Headache: The Journal of Head and Face Pain. 2006;46:1503-1510. Campistol J, Campos J, Casas C, Herranz JL. Topiramate in the prophylactic treatment of migraine in children. Journal of Child Neurology. 2005;20:251-253. Hershey AD, Powers SW, Vockell A-LB, LeCates S, Kabbouche M. Effectiveness of Topiramate in the Prevention of Childhood Headaches. Headache: The Journal of Head and Face Pain. 2002;42:810-818. Unalp A, Uran N, Ozturk A. Comparison of the effectiveness of topiramate and sodium valproate in pediatric migraine. J Child Neurol. 2008;23:1377-1381. Younkin DP. Topiramate in the treatment of pediatric migraine. Headache: The Journal of Head and Face Pain. 2002;42:456. Rossi P, Fiermonte G, Pierelli F. Cinnarizine in migraine prophylaxis: efficacy, tolerability and predictive factors for therapeutic responsiveness. An open-label pilot trial. Funct Neurol. 2003;18:155-159. Togha M, Ashrafian H, Tajik P. Open-label trial of cinnarizine in migraine prophylaxis. Headache. 2006;46:498-502. Togha M, Rahmat Jirde M, Nilavari K, Ashrafian H, Razeghi S, Kohan L. Cinnarizine in refractory migraine prophylaxis: efficacy and tolerability. A comparison with sodium valproate. J Headache Pain. 2008;9:77-82. Headache Classification Committee of The International Headache Society. The International Classification of Headache Disorders, 2nd edn. Cephalalgia. 2004;24(Suppl. 1):1–160. Tonekaboni SH, Ghazavi A, Fayyazi A, Khajeh A, Taghdiri MM, AbdollahGorji F, Azargashb E. Prophylaxis of Childhood Migraine: Topiramate Versus Propranolol. Iran J Child Neurol. 2013 Winter; 7 (1):9-14. Fallah R, AkhavanKarbasi S, Shajari A, Fromandi M. The Efficacy and Safety of Topiramate for Prophylaxis of Migraine in Children. Iran J Child Neurol. 2013 Autumn; 7(4):7-11. Ferraro D, Di Trapani G. Topiramate in the prevention of pediatric migraine: literature review. J Headache Pain. 2008;9:147-150.